1998
DOI: 10.1128/cdli.5.2.176-180.1998
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Serotype and Antibiotic Resistance of Streptococcus pneumoniae Isolates in Two Chilean Cities

Abstract: We compared the incidence of nasopharyngeal colonization byStreptococcus pneumoniae, the serotypes causing mucosal and invasive diseases, and the antibiotic resistance of these strains in patients admitted to three large hospitals and children attending day care centers in two Chilean cities (Santiago and Temuco). The populations in both cities were similar in ethnic background, socioeconomic status, family size, and access to medical care. Significant differences in nasopharyngeal colonization rates, in serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
(33 reference statements)
2
9
0
3
Order By: Relevance
“…The serotype distribution among NP isolates in the present investigation was similar to that found in previous studies in Brazil, the USA and other countries of Latin America and Europe [1,13,19]. Overall, the serotypes isolated from the nasopharynx included the most common serotypes causing invasive disease, with most being represented in the PCV7.…”
Section: Discussionsupporting
confidence: 87%
“…The serotype distribution among NP isolates in the present investigation was similar to that found in previous studies in Brazil, the USA and other countries of Latin America and Europe [1,13,19]. Overall, the serotypes isolated from the nasopharynx included the most common serotypes causing invasive disease, with most being represented in the PCV7.…”
Section: Discussionsupporting
confidence: 87%
“…Five different capsular serotypes commonly associated with penicillin resistance worldwide were found among the 68 isolates of this study. In a recent study, 22 different pneumococcal serotypes were found among nasopharyngeal isolates from Santiago (17). Antibiotic resistance was identified among isolates of five serotypes, and these five serotypes were the same as those found in this study (17).…”
supporting
confidence: 81%
“…Of these 472 pneumococcal cultures, 233 were found to have intermediate penicillin resistance and 77 were resistant. Since a single resistant NP isolate obtained from a day care center in Temuco, Chile, was the only penicillin-resistant isolate reported from an ongoing study in this location (17), it was also included. Sixty-eight of the 78 resistant cultures obtained from a total of 54 asymptomatic children were available for the genotypic analysis done in this study.…”
mentioning
confidence: 99%
“…The tables summarize the most recent data regarding resistance to penicillin among pneumococcal carriers worldwide. By observing the results from studies in which individuals living in different but nearby cities were assessed, it is also possible to observe differences: in children 0 to 2 years of age, 42% were colonized with S. pneumoniae in Santiago compared to 14% in Temuco, both of which are Chilean cities [15]; S. pneumoniae was isolated from 129 of 187 (69%) outpatient children in Gaborone and from 53 of 62 (85%) children in Francistown, two cities in South Africa; this difference was significant (P<0.01) [30]. Therefore, large differences can exist in similar populations located in different regions of the same country.…”
Section: Colonization and Penicillin Resistance Studiesmentioning
confidence: 99%